Functionalized Magnetic Nanomaterial Based on SiO2/Ca(OH)2-Coated Clusters Decorated with Silver Nanoparticles for Dental Applications - Izabell Crăciunescu; George Marian Ispas; Alexandra Ciorîta; Rodica Paula Turcu (Crystals)
In this study, an innovative dental functionalized magnetic nanomaterial was developed by incorporating hydrophilic magnetic clusters as an alternative to conventional isolated magnetic nanoparticles, introducing a novel structural and functional concept in dental applications. The ~100 nm magnetic clusters—composed of densely packed 7 nm Fe3O4 nanoparticles—were sequentially coated with a silica (SiO2) layer (3–5 nm) to improve chemical and mechanical stability, followed by an outer calcium hydroxide [Ca(OH)2] layer to enhance bioactivity and optical integration. This bilayer architecture enables magnetic field-assisted positioning and improved dispersion within dental resin matrices. Silver nanoparticles were incorporated to enhance antimicrobial activity and reduce biofilm formation. The synthesis process was environmentally friendly and scalable. Comprehensive physicochemical characterization confirmed the material’s functional performance. Saturation magnetization decreased progressively with surface functionalization, from 62 to 14 emu/g, while the zeta potential became increasingly negative (from −2.42 to −22.5 mV), supporting its ability to promote apatite nucleation. The thermal conductivity (0.527 W/m·K) closely matched that of human dentin (0.44 W/m·K), and the colorimetric analysis showed improved brightness (ΔL = 5.3) and good color compatibility (ΔE = 11.76). These results indicate that the functionalized magnetic nanomaterial meets essential criteria for restorative use and holds strong potential for future clinical applications.